Design of a 2-Bit wide-angle coding metasurface for bistatic RCS reduction - Huang, Yi Fei; Jiang, Zhongjin; Liu, Lu; Zhang, Hao Chi (Frontiers in Materials, 2022)
In this paper, a 2-bit wide-angle coding metasurface is proposed to reduce the bistatic radar cross section (RCS). The meta-atom of the designed coding metasurface is composed of the microstrip antenna, which has the feature of wide beamwidth, and open stubs loaded at the feeding ports of microstrip antenna. Through elaborately designing the lengths of the open stubs, four different phase coding states with 90° phase difference, called as ‘00’, ‘01’, ‘10’ and ‘11’ state, are realized in a wide-angle range. Simulation results indicate that a reflection amplitude above -1dB and a reflective phase difference of 90° ± 25° in two adjacent coding meta-atoms are achieved. Furthermore, in order to achieve the goal of reducing bistatic RCS without additional optimization algorithms, the generalized Rudin-Shapiro (RS) polynomial is applied to the design of coding sequence of metasurface array. To verify the bistatic RCS reduction, a 16×16 metasurface array is simulated and fabricated. Within 60° of the incidence angles of the plane wave at 8 GHz, good agreements between the simulated and the experimental results show the correctness and the feasibility of the design.